Pengaruh Disiplin Belajar Terhadap Kemampuan Berpikir Kritis Siswa - Salsabila Ananda; Marsofiyati Marsofiyati (Pusat Riset dan Inovasi Nasional, 2025)
Learning discipline is a crucial component that helps students meet their learning objectives, particularly when it comes to honing their critical thinking abilities. The purpose of this study is to examine how learning discipline affects Jakartan high school and vocational high school students' critical thinking abilities. A quantitative approach using a descriptive associative design is the study methodology employed. The sampling procedure was carried out unintentionally mixed with non-probability methods. A Likert scale questionnaire with 40 students as respondents was used to collect the data. The findings demonstrated that, partially and concurrently, studying discipline has a favorable and considerable impact on students' critical thinking abilities. With a t count of 6.176 and a F significance value of 0.000, the positive correlation value is 0.708. According to the analysis of the coefficient of determination (R-Square), learning discipline has a 50.1% impact on critical thinking abilities, with other factors influencing the remaining percentage.